Clinical anatomy and physiology for veterinary technicians - Colville, Thomas P.
Start your veterinary technician education off on the right foot with Clinical Anatomy and Physiology for Veterinary Technicians, 3rd Edition. Combining expert clinical coverage with engaging writing and vivid illustrations, this popular text is the key to helping you understand the anatomic and physiologic principles that will carry you throughout your career. In addition to its comprehensive coverage of the diverse ways in which animal bodies function at both the systemic and cellular levels, the new third edition features a variety of helpful application boxes, vocabulary lists, and Test Yourself questions in every chapter to ensure you have a firm grasp of anatomic structure and its relevance to clinical practice